A new fuzzy DEA network based on possibility and necessity measures for agile supply chain performance evaluation: A case study. (15th June 2023) - Pourbabagol, Hamze; Amiri, Maghsoud; Taghavifard, Mohammad Taghi; Hanafizadeh, Payam
Highlights: Proposing the defuzzification relations of equality constraints with Nec measure. Offering a new fuzzy network slack based model on the basis of necessity measure. The proposed relations combine the Nec equality constraints and network SBM. Using agile supply chain theory to validate the proposed approach. Abstract: With respect to the necessity (Nec) measure, suggesting by Dubois and Prade, there is a dearth of any procedure or formula to deal with equality chance constraints. Therefore, this study attempted to introduce (Nec) and possibility (Pos) equality constraints in a real-case network non-oriented slack based model problem via agile supply chain (ASC) theory. The efficiency of different levels of agility of a dairy supply chain (SC), using a new fuzzy network Date Envelopment Analysis slack based model (FNDEA-SBM) on the basis of (Pos)/(Nec) measures, has been measured in this paper. The measurement took place in a multi-stage process. Since the agility features were rather qualitative in nature, the measures were likely to be delineated subjectively using linguistic expressions and fuzzy data. The application of (Pos)/(Nec) measures and different confidence levels made decision makers capable of getting information of all efficiency and sub efficiency scores through optimistic-pessimistic lenses and taking appropriate decisions on the basis of different optimistic-pessimistic points of view and confidence levels. The validity of the suggested approach was demonstrated through a real-life case study related to Iranian top twenty dairy firms. The results indicated the success of the suggested approach and computations were straightforward.